2018
DOI: 10.4103/jrpp.jrpp_17_88
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing of antimicrobials in Kenya: A cross-sectional pilot study and its implications

Abstract: Objective:The objective of this study was to evaluate the extent of self-medication of antibiotics and dispensing practices in Kenya.Methods:A cross-sectional study was carried out at three selected pharmacies in Nairobi (Kenya), between January and March 2017, targeting principally antibiotic prescriptions for systemic use issued and dispensed as well as antibiotics sold over-the-counter without a prescription. The quality of antibiotics prescribed and dispensed was assessed against key WHO and other criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 21 publications
5
27
0
Order By: Relevance
“…In the community, pharmacists have a vital role as they are often the first healthcare professional that patients contact regarding respiratory/ influenza diseases especially in countries with high patient co-payments, concerns with access to ambulatory healthcare facilities as well as issues of affordability to pay for a physician and their medicines ( Markovic-Pekovic et al., 2017 ; Mukokinya et al., 2018 ; Adunlin et al., 2020 ; Al-Quteimat and Amer, 2020 ; Godman et al., 2020a ). This includes encouraging self care/ hygiene measures including the supplying and wearing of masks and the need for regular hand washing as well as trying to protect patients against stock-outs of pertinent medicines ( Al-Quteimat and Amer, 2020 ; Amariles et al., 2020 ; Haque et al., 2020 ; Ung, 2020 )…”
Section: Resultsmentioning
confidence: 99%
“…In the community, pharmacists have a vital role as they are often the first healthcare professional that patients contact regarding respiratory/ influenza diseases especially in countries with high patient co-payments, concerns with access to ambulatory healthcare facilities as well as issues of affordability to pay for a physician and their medicines ( Markovic-Pekovic et al., 2017 ; Mukokinya et al., 2018 ; Adunlin et al., 2020 ; Al-Quteimat and Amer, 2020 ; Godman et al., 2020a ). This includes encouraging self care/ hygiene measures including the supplying and wearing of masks and the need for regular hand washing as well as trying to protect patients against stock-outs of pertinent medicines ( Al-Quteimat and Amer, 2020 ; Amariles et al., 2020 ; Haque et al., 2020 ; Ung, 2020 )…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, there is a need to educate pharmacists and their assistants about the appropriate management of infections typically seen in ambulatory care given concerns with their knowledge in a number of countries including Pakistan [ 32 , 50 , 53 , 55 , 84 , 85 ]. Studies have shown that educated pharmacists tend to dispense fewer antibiotics for suspected viral infections such as upper respiratory tract infections [ 56 , 86 , 87 ]. Where necessary, patients should be encouraged to visit physicians for their infection.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists and others could also offer online or phone counseling services for patients, promote the rational use of medicines, and potentially offer vaccination services 130,135 . However, this may require improved professionalism among pharmacists and store owners [136][137][138] . Pharmacists and others also need to balance demand and supply of medicines, which is essential in countries with high patient copayments and existing concerns with the availability of medicines in healthcare facilities 126,139 .…”
Section: Role Of Pharmacists and Others In Drug Stores In The Preventmentioning
confidence: 99%